2003
DOI: 10.1542/peds.112.5.e359
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Academic Consequences of Bronchopulmonary Dysplasia and Very Low Birth Weight: 8-Year-Old Outcomes

Abstract: ABSTRACT. Objective. To examine the effects of bronchopulmonary dysplasia (BPD) and very low birth weight (VLBW) on the cognitive and academic achievement of a large sample of 8-year-old children.Methods. Infants who were VLBW and had BPD (n ‫؍‬ 98) or did not have BPD (n ‫؍‬ 75) and term infants (n ‫؍‬ 99) were followed prospectively to age 8. Groups were compared on measures assessing 4 broad areas of functioning: intelligence, achievement, gross motor, and attentional skills. Measures included the Wechsler … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
243
3
27

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 337 publications
(284 citation statements)
references
References 30 publications
11
243
3
27
Order By: Relevance
“…In our previous work with this sample, 17 we demonstrated that steroid use was associated with poorer neurodevelopmental outcomes in the BPD group as a whole; however outcome differences within the BPD group as a function of surfactant treatment were not examined nor were direct comparisons made between children receiving different management strategies. Examining the long-term effects of several treatment options in a BPD cohort that varied in terms of disease severity will help generate hypotheses about how treatment procedures selected to manage BPD are associated with risk factors.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In our previous work with this sample, 17 we demonstrated that steroid use was associated with poorer neurodevelopmental outcomes in the BPD group as a whole; however outcome differences within the BPD group as a function of surfactant treatment were not examined nor were direct comparisons made between children receiving different management strategies. Examining the long-term effects of several treatment options in a BPD cohort that varied in terms of disease severity will help generate hypotheses about how treatment procedures selected to manage BPD are associated with risk factors.…”
Section: Introductionmentioning
confidence: 86%
“…17,18 Recruitment strategies for this study have been detailed elsewhere. [17][18][19] A total of 122 infants with BPD were enrolled in this prospective longitudinal study, however 7 died after enrollment. Ninety-eight and 104 children were seen at 3 and 8 years, respectively.…”
Section: Participantsmentioning
confidence: 99%
“…A melhora no suporte assistencial oferecido às gestantes e a grande evolução tecnológica nos suportes utilizados nas unidades de terapia intensiva (UTI) neonatais aumentaram as possibilidades de sobrevida desses bebês 1,2 . Em pré-termos, as comorbidades associadas, tais como necessidade de suporte ventilatório por perí-odos prolongados, displasia broncopulmonar, hemorragia intracraniana e icterícia, somam-se e contribuem para aumentar os riscos de prejuízos para o desenvolvimento [3][4][5] .…”
Section: Introductionunclassified
“…1,2 Preterm newborns present with several associated comorbidities such as long-term ventilatory support, bronchopulmonary dysplasia, cerebral hemorrhage and jaundice that contribute to increase the risk of developmental impairments. [3][4][5] The direct and indirect consequences related to prematurity can cause damages that impair the child's future development. 2 Approximately 30% of the preterm children develop severe motor impairments and are often diagnosed with cerebral palsy.…”
Section: Introductionmentioning
confidence: 99%
“…Preterm children at low risk for developmental deficits have shown difficulties related to other developmental areas besides the motor area. 5,[8][9][10][11] Studies involving preterm children at school age have found a higher incidence of learning disorders, attention deficits, hyperactivity and behavioral problems in this population. [12][13][14] These future impairments can be reduced with early intervention.…”
Section: Introductionmentioning
confidence: 99%